Anti‐hyperlipidemic and hepatoprotective properties of wheat bran with different particle sizes. (20th November 2018) - Junejo, Shahid A; Zhang, Liang; Yang, Liping; Wang, Naifu; Zhou, Yibin; Xia, Yuesheng; Wang, Haisong
ABSTRACT: BACKGROUND: Wheat bran has been shown to have health‐promoting benefits in relation to diabetes, colorectal cancer, cardiovascular disease, constipation, irritable bowel syndrome, diverticulitis, and gastrointestinal disease. However, its effects on obesity, hyperglycemia, hepatotoxicity, and hyperlipidemia are not yet clear. The effects of the consumption of wheat bran of different particle sizes (coarse, 427.55 µm versus ultra‐fine, 11.63 µm) on body weight, serum glucose, liver, and blood lipid metabolism levels in high‐fat‐diet induced rats fed for 5 weeks were investigated. RESULTS: The high‐fat diet significantly increased body weight, serum glucose, serum and liver lipids, and malondialdehyde levels. However, addition of coarse and ultra‐fine wheat bran to a high‐fat diet decreased weight gain, reduced the levels of serum and liver total cholesterol, triglycerides, malondialdehyde, serum low‐density lipoprotein, and serum glucose, and improved serum high‐density lipoprotein. Moreover, when two particle sizes were compared, the highest impact was exhibited by the wheat bran containing the larger particle size. CONCLUSIONS: The results suggest that micronized wheat bran significantly improves anti‐hyperlipidemic and hepatoprotective properties that might provide a safeguard to protect humans against metabolic syndrome abnormalities and other acute, recurrent, or chronic diseases. © 2018 Society of Chemical Industry